Between couch and piano : psychoanalysis, music, art and neuroscience - Rose, Gilbert J., 1923- (Brunner-Routledge, 2004)
Between Couch and Piano links well-established psychoanalytic ideas with historical and neurological theory to help us begin to understand from a psychoanalytic perspective some of the reasons behind music's ubiquity and power.